The Irish unit fund industry: structure and performance - Kenneally, Martin; Gallagher, Liam (Economic & Social Studies, 1992)
An outline of the size, structure, functioning and price history of the Unit Fund industry in Ireland is sketched for the period 1983-1990. Some traditional performance measures are motivated and augmented by more recent measures which attempt to identify overall fund performance and decompose its selection, diversification and timing components. An empirical appraisal of the performance of the 16 funds extant over the sample period is conducted and absolute and comparative rankings are established. The results are not supportive of superior performance ability by Irish Unit Fund managers.
Keywords: Unit funds; Investments; Ireland